Mental healthcare in Brazilian spiritism - Kurz, Helmar, 1975- author.
1 online resource.
Keywords: "This volume addresses the diversification of mental healthcare provision and patients' health-seeking behavior by putting Brazilian Spiritism and its translocal relations at the center of its inquiry. Comparative chapters document and critically assess the affective arrangements of Spiritist spaces in Brazil and Germany and how practices contribute to healing and the diversification of a globally circulating mental health agenda. The book addresses the human experience within Spiritist psychiatric clinics and affiliated Spiritist centers in Brazil, which in migratory contexts also have connections to Germany. Chapters interrogate the spaces where people in- and outside Brazil engage in implementing Spiritist practices in mental healthcare, introducing the aesthetics of healing as a conceptual tool to understand interactions between religion and medicine more broadly. Establishing a novel analytical and interdisciplinary perspective on embodied aspects of sensory experience and perception, this compelling volume will be of interest to scholars, researchers, and postgraduate students involved with mental health research, medical anthropology, spiritualism, and cross-cultural psychology. Practitioners in the fields of transcultural psychiatry and the sociology of religion will also find the volume of use"--